Verification of Biodegradation Efficiency of Textile Wastewater Using Ecotoxicity Test on Sinapis Alba - PAVLÍKOVÁ, Marie (GeoScience Engineering, 2020)
The impact of biodegradation of textile wastewater using the microorganism Phoma sp. was assessed and verified. The resulting ecotoxicity of biodegraded wastewater on seeds of Sinapis alba was evaluated in accordance with the Methodological Instruction of the Ministry of the Environment of the Czech Republic for the evaluation of toxicity of waste and aqueous extracts (Decree 94/2016 Coll.). Wastewater from the textile industry produced in connection with wool dyeing was tested, the first sample (A) was taken immediately after the dyeing process, the second sample (B) was taken from the first rinse with 20% dilution. The biodegradation efficiency of textile wastewater was confirmed on the length of the tested plants’ seed roots. The root length of the sample 3A increased by 265.79 %, while 3B increased by more than 118 %, compared to the control sample. The obtained results indicate a significant impact of microbial biodegradation, with a direct effect on the length of the root of germinated seeds. Keywords: Ecotoxicity; Microorganisms; Textile industry; Wastewater. DOI 10.35180/gse-2020-0040